2022
DOI: 10.1039/d2cp02362h
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative electron attachment dynamics of carbon disulfide and violation of axial recoil approximation near 6 eV resonance

Abstract: Complete dissociation dynamics of low-energy electron attachment to carbon disulfide have been studied using the velocity slice imaging (VSI) technique. The ion yields of the different fragment anions produced due...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…One possible explanation could be that the excess energy is distributed as the internal excitation (rovibrational excitation) of the neutral conjugate (CO), which was not possible for the dissociation of a diatomic molecule like CO and O 2 . This type of excess energy redistribution was also found in low-energy DEA to triatomic and other polyatomic molecules [31,62]. From the variation of most probable kinetic energy with the incident electron energy, the authors found that the ion kinetic energy first increases with the increasing electron energy and then gets locked.…”
Section: Triatomic Molecule: Comentioning
confidence: 60%
See 3 more Smart Citations
“…One possible explanation could be that the excess energy is distributed as the internal excitation (rovibrational excitation) of the neutral conjugate (CO), which was not possible for the dissociation of a diatomic molecule like CO and O 2 . This type of excess energy redistribution was also found in low-energy DEA to triatomic and other polyatomic molecules [31,62]. From the variation of most probable kinetic energy with the incident electron energy, the authors found that the ion kinetic energy first increases with the increasing electron energy and then gets locked.…”
Section: Triatomic Molecule: Comentioning
confidence: 60%
“…The schematic of a simple VMI spectrometer is shown in figure 1(b). This is one of the most advanced systems for electron-molecule collision studies and is widely used by several groups [28,31,40]. The basic procedure in the experiment entails the interaction of an electron beam and a molecular beam, where one of them is in pulsed mode.…”
Section: Vmimentioning
confidence: 99%
See 2 more Smart Citations
“…At energies above 4 eV, DEA is proceeding via core excited resonances of the CS bond in a mechanism similar to CS 2 . 131 The most intense DEA channels opening at this energy are leading to S − and (TU-S) − . However, the ion yield of the second most intense decomposition product of the molecule SCN − is slightly shifted towards lower energy, which can be a result of the contribution from the high π* shape resonance to this DEA channel.…”
Section: Dna Componentsmentioning
confidence: 99%